Recent Record of Greater False Vampire Bat (Lyroderma lyra, E. Geoffroy,1810) in the Lower South Bank Plain of the Brahmaputra Valley, Assam, India - Talukdar, Jugal Kishore; Haloi, Akshay Kr. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The study of bats in India is often viewed as limited and underexplored. In 1810, French scientist E. Geoffroy published the first scientific description of the bat fauna of India, focusing on Lyroderma lyra sp. also known as Greater false vampire bat from Madras.This account is deemed the first documentation of the bat species present in the country. Subsequently, Hinton and Lindsay (1926) and Sinha (1999) reported sightings of the species in the few localities of Assam. The current research pinpointed three distinct roost sites (S-A; S-B; S-C) where L. lyra has been observed to roost in varied habitats. The species recorded from three distinct locations exhibits an average forearm length of 68.1±1.76 mm and an average body mass of 55.6±4.04 g. Lyroderma lyra is recognized by its bifid tragus and a long, upright, and simple noseleaf measuring 10. 8± 0.7 mm, which is significantly larger than the 6.5 mm noseleafin comparision to M. spasma (the other species in the Megadermatidae family). L. lyra, part of the Megadermatidae family, uses vision and passive listening to hunt prey, even in complete darkness.It plays a crucial role in pest and bio-resource management, regulating insect populations in forests and agro-ecosystems.